RAF Suppression Synergizes with MEK Inhibition in KRAS Mutant Cancer Cells - Simona Lamba; Mariangela Russo; Chong Sun; Luca Lazzari; Carlotta Cancelliere; Wipawadee Grernrum; Cor Lieftink; Rene Bernards; Federica Di Nicolantonio; Alberto Bardelli (Cell Reports, 2014)
KRAS is the most frequently mutated oncogene in human cancer, yet no therapies are available to treat KRAS mutant cancers. We used two independent reverse genetic approaches to identify components of the RAS-signaling pathways required for growth of KRAS mutant tumors. Small interfering RNA (siRNA) screening of 37 KRAS mutant colorectal cancer cell lines showed that RAF1 suppression was synthetic lethal with MEK inhibition. An unbiased kinome short hairpin RNA (shRNA)-based screen confirmed this synthetic lethal interaction in colorectal as well as in lung cancer cells bearing KRAS mutations. Compounds targeting RAF kinases can reverse resistance to the MEK inhibitor selumetinib. MEK inhibition induces RAS activation and BRAF-RAF1 dimerization and sustains MEK-ERK signaling, which is responsible for intrinsic resistance to selumetinib. Prolonged dual blockade of RAF and MEK leads to persistent ERK suppression and efficiently induces apoptosis. Our data underlie the relevance of developing combinatorial regimens of drugs targeting the RAF-MEK pathway in KRAS mutant tumors.